Standardization of Peabody Developmental Motor Scales in Children Aged 60-71 Months in Shiraz - Seyed Ali Reza Derakhshan-Rad; Ali Hossein Sazmand (University of Social Welfare and Rehabilitation Sciences, 2011)
Objective : The evaluation of the quality of motor abilities by the means of a standard instrument is important diagnostic parameter which leads to discovery of probable disabilities and developmental delay in childhood. Hence, to achieve a standard complete tool for measuring of indigenous children motor abilities by way of standardization of Peabody Developmental Motor Scales (PDMS) was the aim of this study. Materials & Methods : In this descriptive study 150 normal children aged 60 - 71 months with identical gender distribution were selected by multiple cluster sampling among kindergartens of 6 urban districts of Shiraz and their gross and fine motor abilities were evaluated by PDMS. Reliability and validity of PDMS was examined initially. Afterwards, in order to standard the scale according to study population motor abilities, the raw scores which result of the evaluation of motor performance, transformed to standard scores. Results: High correlation coefficients proved that PDMS was reliable and valid. With reference to the reliability, as a case in point, Intraclass correlation coefficient (ICC) repeated test by the same therapist was 0.987 for gross motor scale and 0.971 for fine motor scale. Compiling the standardized tables by transforming raw scores to standard scores are the other significant findings of the study. Conclusion: Clinicians and therapists could utilize PDMS as a standard and accurate device for examining motor characteristics of 60 - 71 months children. And, they can make a correct decision by evaluating the patient first and then matching up the data with standardized table based on this study.